High-efficiency vertical-structure GaN-based light-emitting diodes on Si substrates. Issue 7 (24th January 2018) - Wang, Wenliang; Lin, Yunhao; Li, Yuan; Li, Xiaochan; Huang, Liegen; Zheng, Yulin; Lin, Zhiting; Wang, Haiyan; Li, Guoqiang
Abstract : High-quality GaN-based light-emitting diode (LED) wafers have been grown on Si substrates by metal–organic chemical vapor deposition by designing epitaxial structures with AlN/Al0.24 Ga0.76 N buffer layers and a three-dimensional (3D) GaN layer. Abstract : High-quality GaN-based light-emitting diode (LED) wafers have been grown on Si substrates by metal–organic chemical vapor deposition by designing epitaxial structures with AlN/Al0.24 Ga0.76 N buffer layers and a three-dimensional (3D) GaN layer. The AlN/Al0.24 Ga0.76 N buffer layers are directly grown on Si substrates to provide the large compressive stress to balance the tensile stress introduced during the cooling process, and the 3D GaN layer is grown on the Al0.24 Ga0.76 N buffer layer to reduce the dislocation density of GaN epitaxial films. The as-grown GaN-based LED wafers exhibit very high crystalline quality with full-width at half-maximums for GaN(0002) and GaN(10−12) of 300 and 345 arcsec, respectively, and an internal quantum efficiency of ∼80.1%. Afterwards, the LED wafers are fabricated into vertical-structure LED chips with a size of 1 × 1 mm 2 by the standard process. The as-prepared vertical-structure LED chips exhibited a light output power of 569 mW with a working voltage and a wall-plug efficiency of 2.82 V and 57.6%, respectively, at a current of 350 mA. These high-efficiency vertical-structure LED chips are expected to find a wide range of applications in solid-state lighting fields.